Influence of Zeolite, Kaolin, and Chitosan on the Growth and Productivity of Strawberry - Walid F. A. Mosa; Khalid Almutairi; Krzysztof Górnik; Lidia Sas-Paszt (BioResources)
Although chemical fertilizers increase crop productivity, they have undesirable effects on the environment, soil fertility, and negatively influence fruit shelf life and quality. Therefore, the application of plant biostimulants and biostimulant-like substances has become necessary to improve the availability and absorption of nutrients, enhance growth, yield, quality, and tolerance to abiotic and biotic stresses, and serve as an alternative to mineral fertilizers. Therefore, this study investigated the influence of zeolite, kaolin (KL), and chitosan (Cs) in alleviating abiotic stress and improving productivity and quality of strawberry plants. Strawberry plants were soil fertilized by zeolite at 0, 2, and 3 kg and then they were sprayed with 2% g/L KL + 500 ppm Cs, 4% KL + 1000 ppm Cs, and 6% KL + 1500 ppm Cs. The individual application of zeolite improved the performance of strawberry plants, and its influence greatly increased with the combination spraying of different combinations from KL + Cs. The highest increments resulted from the application of 3 and 2 kg of zeolite combined with the spraying of 4% KL + 1000 ppm Cs and 6% KL + 1500 ppm Cs compared to non-treated plants.